Equilibrium Studies on Pd(II)–Amine Complexes with Bio-Relevant Ligands in Reference to Their Antitumor Activity - Shoukry, Mohamed M.; van Eldik, Rudi (International Journal of Molecular Sciences, 2023)
This review article presents an overview of the equilibrium studies on Pd-amine complexes with bio-relevant ligands in reference to their antitumor activity. Pd(II) complexes with amines of different functional groups, were synthesized and characterized in many studies. The complex formation equilibria of Pd(amine)2+ complexes with amino acids, peptides, dicarboxylic acids and DNA constituents, were extensively investigated. Such systems may be considered as one of the models for the possible reactions occurring with antitumor drugs in biological systems. The stability of the formed complexes depends on the structural parameters of the amines and the bio-relevant ligands. The evaluated speciation curves can help to provide a pictorial presentation of the reactions in solutions of different pH values. The stability data of complexes with sulfur donor ligands compared with those of DNA constituents, can reveal information regarding the deactivation caused by sulfur donors. The formation equilibria of binuclear complexes of Pd(II) with DNA constituents was investigated to support the biological significance of this class of complexes. Most of the Pd(amine)2+ complexes investigated were studied in a low dielectric constant medium, resembling that of a biological medium. Investigations of the thermodynamic parameters reveal that the formation of the Pd(amine)2+ complex species is exothermic.
CRIS-Team Scopus Importer:2023-03-24
Keywords: bio-relevant ligands; Pd-amine complexes; speciation studies; stability constants; thermodynamic parameters